GREEN SYNTHESIS NANOMAGNETIC MnFe2O4 USING BREADFRUIT LEAF EXTRACT (Artocarpus altilis) AND ANTI-BACTERIAL ACTIVITY TEST AGAINST E.Coli AND S. Aureus - Bella Safitri; Poedji Loekitowati Hariani; Heni Yohandini Kusumawati (Analit : Analytical and Environmental Chemistry, 2024)
In this research, breadfruit (Artocarpus Altilis) leaf extract has been used to synthesize nanomagnetic MnFe2O4. The resulting nanomagnetic characterization uses a Vibrating Sample Magnetometer (VSM) to determine magnetic properties, phase type and crystal size using analytical X-Ray Diffraction (XRD), morphology and element composition using Scanning Electron Dispersive X-ray Spectroscopy (SEM-EDX) and functional groups using Fourier Transform Infra Red (FTIR). MnFe2O4 obtained was tested for antibacterial activity against the gram-positive bacteria E. Coli and S.aureus. The result of the VSM characterization has magnetic property of 47.76 emu/g, the nanomagnetic XRD characterization was successfully synthesized with a peak appearing at an angle 2Î¸= 30.02 °, 35.28 °, 44.53 °, 56.65 °, dan 62.25 °, which corresponds to the crystal plane (220), (311), (400), (511) and (440)   showed an average crystal size of 25.85 nm, SEM results with various magnifications showed the formation of aggregates or chunks of unequal size, as well as the presence of Mn-O and Fe-O groups in FTIR analysis. This research showed that the nanomagnetic compound MnFe2O4 obtained from green synthesis has antibacterial properties against gram-positive bacteria E. Coli and S. aureus with a Minimum Inhibitory Capability (MIC) value of 2000 ppm. These results indicated that nanomagnetic compounds using the green synthesis method have the potential to be applied to gram-positive bacteria E.Coli and S.aureus.